Measuring financial integration in the euro area - Lieven Baele; Annalisa Ferrando; Peter Hördahl; Elizaveta Krylova; Cyril Monnet (European Central Bank (ECB), 2004)
In this paper, we present a set of specific measures to quantify the state and evolution of financial integration in the euro area. Five key markets are considered, namely the money, corporate bond, government bond, credit and equity markets. Building upon the law of one price, we developed two types of indicators that can be broadly categorised as price-based and news-based measures. We complemented these measures by a number of quantity-based indicators, mainly related to the evolution of the home bias. Results indicate that the unsecured money market is fully integrated, while integration is reasonably high in the government and corporate bond market, as well as in the equity markets. The credit market is among the least integrated, especially in the short-term segment.
Keywords: G12; G14; G15; G18; 330; financial integration; EMU; law of one price.; Finanzmarkt; Finanzsektor; EU-Binnenmarkt; Messung; Eurozone; EU-Staaten